Maternity leave: (A study of its impact on female employees in organisations in Dhaka Bangladesh) - Chowdhury, Shaan Ahmed (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.